Research on sustainable supply capacity of critical metals in China’s new energy vehicles under coupled allocation of primary and secondary resources - Xuesong, DONG; Jinyu, CHEN; Meimei, HU (Zi yuan ke xue, 2025)
[Objective] This study aims to explore the impact trends of future new energy vehicle development on the demand and sustainable supply capacity of critical metals such as lithium, cobalt, and nickel in China. From the perspective of coupled allocation of primary and secondary resources, combined scenarios are proposed to ensure their sustainable supply, thereby providing a reference for resolving critical metal constraints during the energy transition and ensuring national resource security. [Methods] By integrating scenario analysis with a stock-driven material flow model, this study assessed the sustainable supply capacity of critical metals for new energy vehicles in China from 2010 to 2023. Furthermore, this study simulated the impact of coupled primary and secondary resources on critical metal demand under scenarios of different electric vehicle market scales and battery technology pathways from 2024 to 2050, and evaluated the sustainable supply capacity of critical metals across multiple scenarios. [Results] (1) From 2010 to 2023, China’s critical metal supply for new energy vehicles was primarily based on primary resources. In 2023, the demand for lithium and cobalt in this field reached 36000 tons and 18000 tons, respectively. The nickel-cobalt-manganese (NCM) technology exhibited an evolution trend of “high nickel and low cobalt”. (2) Extending the lifespan of batteries could simultaneously reduce the demand for lithium, cobalt, and nickel. The evolution of electrochemical technologies could significantly reduce the demand for cobalt and nickel while improving their sustainable supply capacity. (3) The combined scenarios integrated the advantages of supply- and demand-side scenarios, exerting positive impact on the resource sustainability index (SI), accumulated primary resource consumption (AC), secondary resource expansion multiplier (MU), and supply-demand ratio (SDR) for lithium, cobalt, and nickel. This could alleviate the bottleneck of resource constraints to some extent. [Conclusion] To ensure the sustainable development of China’s new energy vehicle industry and resource security, it is essential to advance the development of electrochemical technologies, improve the utilization efficiency of power batteries, optimize policy combinations for the coupled allocation of primary and secondary resources, and establish a strategic reserve system for critical metals.